Identification and characteristics of a novel testis-specific gene, Tsc21, in mice and human - Yu, Zhendong; Tang, Aifa; Gui, Yaoting; Guo, Xin; Zhu, Hui; Long, Yun; Li, Zeting; Cai, Zhiming (Molecular biology reports, 2007)
Testis-specific genes are essential for spermatogenesis in mammalian male reproduction. We have identified a novel gene, Tsc21, exclusively expressed in mice and human testes from the results of the Affymetrix Genechip analysis in the six developmental stages of testis of postnatal Balb/C mice. The full cDNA length of Tsc21 was 810 bp, with a 543 bp open reading frame encoding a 180 amino acids protein with a predicted molecular weight of 21.040 kDa. A Blast search in the mouse genome database localized the Tsc21 gene to mice chromosome 6C3. Multiple amino acid sequence alignment of human, mouse, and rat homologous genes showed that mice Tsc21 protein was highly homologous with the human Tsc21 gene (70%) and rat Tsc21 gene (86%). The results of reverse transcriptase-polymerase chain reaction analysis showed that the mice Tsc21 is exclusively expressed in the testis and epididymis of mice, and its expression is only detected after the mice is 35 days old. Human Tsc21 is also exclusively expressed in testis of human. Considering the expression profile Tsc21 in mice and human, we propose that Tsc21 may play a role during mammalian male spermatogenesis. Our study should be a basis for function characterization of the Tsc21 gene, leading to the elucidation of the molecular events underlying mammalian male reproduction.